2017
DOI: 10.18632/oncotarget.17869
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ERK enhances the cytotoxic effect of the novel PI3K and mTOR dual inhibitor VS-5584 in preclinical models of pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a deadly disease in urgent need of newer therapeutic modalities. Majority of patients with PDAC have mutations in KRAS, which unfortunately remains an ineffectual target. Our strategy here is to target KRAS downstream effectors PI3K and mTOR. In this study, we investigated the antitumor efficacy of the novel PI3K and mTOR dual inhibitor VS-5584 in PDAC. Our data shows that PI3K/mTOR dual inhibition causes ERK activation in all tested PDAC cell lines. Although the MEK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
(47 reference statements)
4
19
1
Order By: Relevance
“…In contrast to the reports of other PI3/mTOR inhibitors such as BEZ-235, PKI-587, GDC-0980, and VS-5584 used in pancreatic cancer, we found that CMG002 did not induce a compensatory activation of MEK/ERK pathway in our GC cell lines ( Supplementary Fig. S1 ) ( Ning et al, 2017 ; Soares et al, 2015 ). We hypothesize that the differential activation of MEK/ERK pathway by PI3K/mTOR dual inhibitors may be idiosyncratic to individual inhibitors acting on specific cancer subtypes or cancer cell lines.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the reports of other PI3/mTOR inhibitors such as BEZ-235, PKI-587, GDC-0980, and VS-5584 used in pancreatic cancer, we found that CMG002 did not induce a compensatory activation of MEK/ERK pathway in our GC cell lines ( Supplementary Fig. S1 ) ( Ning et al, 2017 ; Soares et al, 2015 ). We hypothesize that the differential activation of MEK/ERK pathway by PI3K/mTOR dual inhibitors may be idiosyncratic to individual inhibitors acting on specific cancer subtypes or cancer cell lines.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, total S6, the protein downstream of mTOR, which also decreased consistently, became less than 10% of pre-treatment values within 60 minutes of CMG002 treatment in both cell lines. We were concerned that blockade of the PI3K/AKT/mTOR pathway could shunt the cellular response toward a compensatory activation of the mitogen-activated protein kinase kinase/extracellular signal-regulated kinase (MEK/ERK) pathway based on similar reports from other PI3K/mTOR dual inhibitors ( Ning et al, 2017 ; Soares et al, 2015 ); however, we did not observe increased ERK phosphorylation after 60 minutes of treatment with CMG002 in either AGS or NUGC3 cells, regardless of EBV infection ( Fig. 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Lower AKT levels result in a significant reduction of cell proliferation and accumulation of cells in G0/G1 phase, besides a decreased metabolic activity. Furthermore, it is worth mentioning that mTORC2 blockade does not trigger ERK1/2 phosphorylation as a feedback mechanism to balance the lack of pro-survival stimuli, similar to other tumor cells (Mendoza et al, 2011 ; Ning et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we find that, in general, PDAC is characterised by pervasive RTK, MAPK and PI3K-mTOR alterations [ 1 , 8 , 58 , 59 ] and that over 90% of the potentially oncogenic alterations occur in genes that are directly involved in the RTK, MAPK and PI3K-mTOR signalling pathways. It is well established that PDAC tumours frequently respond to MAPK and/or PI3K-mTOR pathway inhibitors [ 58 , 60 ]. While cases where these inhibitors have failed to provide therapeutic benefits have highlighted the heterogeneity of PDAC, they have also emphasised the importance of finding additional drugs that are either more generally applicable to PDAC treatment, or which can be used to target the signalling pathways that are most relevant for specific PDAC subtypes [ 60 62 ].…”
Section: Discussionmentioning
confidence: 99%